(untitled) (Global Journal of Human-Social Science, 2020)
The aims of paper is to examine the effect of the quality of political institution including the control of corruption and the absence of political violence on the relation between trade and economic growth of a sample 5 Central African countries over the period from 1995 to 2018. Using the Generalized Moment Method (GMM), the results reveal that (i) trade positively influences economic growth (ii) corruption control improves the positive effect of trade on economic growth (iii) the absence of political violence does not influence the effect of trade on economic growth. In order to benefit from growth led by trade, corruption control matters. In terms of economic policy implications, our results urge the political authorities to strengthen the control of trade facilitate the accession of their countries to the club of emerging economies.